MAPK cascade‐mediated regulation of pathogenicity, conidiation and tolerance to abiotic stresses in the entomopathogenic fungus Metarhizium robertsii. (4th February 2016) - Chen, Xiaoxuan; Xu, Chuan; Qian, Ying; Liu, Ran; Zhang, Qiangqiang; Zeng, Guohong; Zhang, Xin; Zhao, Hong; Fang, Weiguo
Summary: M etarhizium robertsii has been used as a model to study fungal pathogenesis in insects, and its pathogenicity has many parallels with plant and mammal pathogenic fungi. MAPK (Mitogen‐activated protein kinase) cascades play pivotal roles in cellular regulation in fungi, but their functions have not been characterized in M . robertsii . In this study, we identified the full complement of MAPK cascade components in M . robertsii and dissected their regulatory roles in pathogenesis, conidiation and stress tolerance. The nine components of the Fus3, Hog1 and Slt2‐MAPK cascades are all involved in conidiation. The Fus3‐ and Hog1‐MAPK cascades are necessary for tolerance to hyperosmotic stress, and the Slt2‐ and Fus3‐MAPK cascades both mediate cell wall integrity. The Hog1 and Slt2‐MAPK cascades contribute to pathogenicity; the Fus3‐MAPK cascade is indispensable for fungal pathogenesis. During its life cycle, M . robertsii experiences multiple microenvironments as it transverses the cuticle into the haemocoel. RNA‐seq analysis revealed that MAPK cascades collectively play a major role in regulating the adaptation of M . robertsii to the microenvironmental change from the cuticle to the haemolymph. The three MAPKs each regulate their own distinctive subset of genes during penetration of the cuticle and haemocoel colonization, but they function redundantly to regulate adaptation to microenvironmental change.